Analisis Faktor-Faktor Produktivitas Kerja Pembatik di Industri Batik Farras, Kecamatan Lendah - Umi Masrohatun Khasanah; Agus Suwarni; Narto Narto (Poltekkes Kemenkes Yogyakarta, 2017)
Productivity is not only aimed to get the work result maximally, but quality of the work is also important. This study was aimed to determine what factors are associated with labor productivity in Batik Farras industry which is located in Kecamatan Lendah. The type of this research was survey with cross sectional design. The study subjects were all 30 workers of Batik Farras. The instruments used in this study were labor productivity form, weight scales and microtoise to measure body height. The data analysis used regression statistical test at 0,05 significance level. The study results concluded that there is no relationship between age and labor productivity (p-value = 0,093), there is relationship betwen labor period and labor productivity (pvalue = 0,004), and there is no relationship between nutritional status and labor productivity (pvalue = 0,248).